Association between body roundness index and osteoarthritis/rheumatoid arthritis: a cross-sectional study - Tao Gao; Zhi-Yu Chen; Tao Li; Xu Lin; Hai-Gang Hu; Jian-Dong Tang; Chao Wu (Scientific Reports)
Abstract To explore the relationship between the Body Roundness Index (BRI) and the prevalence of osteoarthritis (OA) and rheumatoid arthritis (RA) among American adults, providing new insights for identifying OA and RA in adults. We analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2015–2023 and conducted a large cross-sectional study. BRI was calculated based on body measurements, while OA and RA cases were identified through questionnaires. Participants under 20 years of age and those with incomplete data were excluded. Weighted multivariate logistic regression models, restricted cubic spline (RCS) functions, and stratified analyses were used to assess the relationship between BRI levels and the prevalence of OA and RA in American adults. To further evaluate BRI’s diagnostic potential for OA and RA, receiver operating characteristic (ROC) curves were employed to analyze and calculate the area under the curve (AUC). After screening, 17,544 participants were included, with 2,382 cases of OA (13.58%) and 987 cases of RA (5.63%). Multivariate logistic regression analyses showed a positive correlation between BRI and OA prevalence in American adults in both the unadjusted and adjusted models. A similar correlation was observed for RA in the unadjusted and partially adjusted models (P < 0.001), but the fully adjusted model showed no significant association between BRI and RA (P > 0.05). In the unadjusted model, the prevalence of OA in the highest BRI quartile was 3.47 times than that of the lowest quartile (95% CI: 2.84, 4.24, P < 0.001). Even in the fully adjusted model, the prevalence of OA in the highest BRI quartile remained 1.46 times higher than that of the lowest quartile (95% CI: 1.02, 2.08, P < 0.05). RCS curves demonstrated a non-linear relationship between BRI and both OA and RA, with a significant increase in prevalence as BRI levels rose (P < 0.001). Subgroup analyses and forest plots indicated a positive correlation between BRI and OA and RA in most subgroups (P < 0.05). ROC curves showed that BRI had a better predictive ability for OA and RA risk compared to BMI. There is a significant positive correlation between BRI and the prevalence of OA and RA in American adults, especially OA. Maintaining a lower BRI may help prevent the onset of OA and RA.